Upregulation of microRNA-224 is associated with aggressive progression and poor prognosis in human cervical cancer - Shen, Shu-na (BioMed Central, 2013)
OBJECTIVE: Accumulating evidence for differential expression of microRNA-224 (miR-224) in various types of human cancer suggests that it may be play a crucial role in tumor biology. The previous microarray detection also shown that miR-224 was one of miRNAs with significant upregulation in cervical cancer tissues relative to adjacent normal tissues. However, little is known about the function of miR-224 in human cervical cancer. The aim of this study was to investigate the clinical significance of miR-224 expression in cervical cancer. METHODS: MiR-224 expression in 126 pairs of fresh human cervical cancer and adjacent normal tissues was measured by real-time quantitative RT-PCR assay. RESULTS: miR-224 expression was significantly upregulated in cervical cancer tissues when compared with corresponding adjacent normal tissues (P < 0.001). It was also significantly higher in the cancerous tissues of patients with advanced FIGO stage cervical cancer than those with early FIGO stage (P = 0.02). In addition, miR-224 was expressed at significantly higher levels in lymph node metastasis-positive patients than in lymph node metastasis-negative patients (P = 0.008). Moreover, we found that lesser differentiated tumors expressed higher miR-224 (P = 0.03). Finally, there were sufficient evidence to confirm its value in the status of vascular invasion (P = 0.01) and human papillomavirus (HPV) infection (P = 0.02) in cervical cancer. More importantly, Kaplan-Meier analysis showed that cervical cancer patients with high miR-224 expression tend to have shorter overall survival. In multivariate analysis stratified for known prognostic variables, miR-224 was identified as an independent prognostic marker. CONCLUSION: Our data indicated that miR-224 upregulation was associated with aggressive progression and poor prognosis in cervical cancer. MiR-224 was identified for the first time as an independent marker for predicting the clinical outcome of cervical cancer patients. VIRTUAL SLIDES: The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/2170449349527493